Exploring the Transition of Public Librarians to "Prompt Librarians" from the Perspective of New Quality Productive Forces - SUN Lijuan (Nongye tushu qingbao xuebao)
[Purpose/Significance] With the rapid development of generative artificial intelligence (AI) and large language models (LLMs), the role of "prompt librarians" has emerged. This study constructs a theoretical framework for prompt librarians and explores the rationality, feasibility, and significance of the transition of librarians to this role from the perspective of new quality productive forces. Driven by the new quality productive forces represented by AI, transforming librarians into prompt librarians can not only optimize application scenarios and user experience, but also improve work efficiency and effectively promote the intelligent transformation of libraries. There is currently no research on this topic in the existing literature. This study, for the first time, proposes a theoretical framework for prompt librarians and the implementation path for the transition of librarians, filling the research gap in this area. [Method/Process] Through a review of relevant national and international literature, this study examines the impact of AI on the role and positioning of librarians within the library industry. Taking the new quality productive forces as the theoretical foundation and driving factor, the study explains the necessity of the transition of public librarians to prompt librarians, and analyzes the rationality, feasibility, and significance of this transition. Furthermore, a theoretical framework for prompt librarians is constructed, encompassing concepts, scope of functions, work processes, and core competencies. Additionally, through the method of literature review and online surveys, the study examines the current status of information and knowledge services in public libraries, focusing on the top thirty libraries ranked by online influence in China. It identifies the major challenges faced by librarians in the transition. Based on the theoretical framework of prompt librarians and real-world challenges, the study explores the implementation path for the transition of librarians to prompt librarians, ensuring the scientific, logical, and innovative nature of the research. [Results/Conclusions] As an emerging role that combines the library industry with AI technology, prompt librarians, driven by user needs, explore the unique resources of their collections in depth, revitalizing literature, diverse information resources, and other materials through AI pathways. They act as guides and translators between knowledge and AI, effectively driving the intelligent transformation of libraries. However, the transition of librarians faces many challenges. To facilitate a smooth transition, this study proposes implementation pathways, such as the establishment of dedicated prompt librarian positions, a "three-step leap" training model for librarians, robust top-level planning, the construction of multi-modal resource service platforms, AI ethics considerations, and interdisciplinary collaboration. Through these explorations, the study aims to provide innovative ideas and practical guidance for the transition of librarians in the AI era, enrich research on the application scenarios of new quality productive forces, and enhance the service quality and competitiveness of libraries.